Epigenomic preconditioning of peripheral monocytes determines their transcriptional response to the tumor microenvironment - Máté Kiss; Laszlo Halasz; Eva Hadadi; Wilhelm K. Berger; Petros Tzerpos; Szilard Poliska; Daliya Kancheva; Aurélie Gabriel; Romina Mora Barthelmess; Ayla Debraekeleer; Jan Brughmans; Yvon Elkrim; et al. (Genome Medicine)
Abstract Background Monocytes are recruited to tumors and undergo transcriptional reprogramming resulting in tumor-promoting functions. Epigenomic features, such as post-translational modification of histones and chromatin accessibility, are key determinants of transcription factor binding and thereby play an important role in controlling transcriptional responses to the tissue environment. It remains unknown whether systemic tumor-associated signals could alter the epigenomic landscape of peripheral monocytes before they reach the tumor, thus shaping their subsequent response to the tumor microenvironment. Methods We used a combination of genome-wide assays for chromatin accessibility and multiple histone modifications (H3K4me1, H3K4me3, H3K27ac) in a mouse tumor model to investigate changes in the epigenomic landscape of peripheral monocytes. We then integrated these epigenomic data with transcriptomic data to link altered regulatory elements to gene expression changes in monocytes occurring in the periphery or during tumor infiltration. Results We found that tumor-induced systemic inflammation was associated with transcriptional and epigenomic preconditioning of peripheral monocytes. The distal tumor caused extensive remodeling of both H3K4me3+ promoters and H3K4me1+ enhancers. Specifically, this involved the repression of interferon-responsive regulatory elements as well as the establishment of enhancers harboring binding motifs for transcription factor families downstream of pro-inflammatory signaling, such as C/EBP, AP-1, and STAT. Reprogrammed enhancers in peripheral monocytes were linked to sustained gene expression changes that persisted after tumor infiltration. In addition, key pro-tumor genes upregulated in tumor-infiltrating monocytes showed epigenetic priming already in the circulation. Conclusions These results suggest that cancer-associated remodeling of the epigenomic landscape in peripheral monocytes can shape the gene expression programs they acquire in the tumor, highlighting the role of the epigenome in redirecting monocyte function to support cancer progression.